2015
DOI: 10.1039/c5tc01951f
|View full text |Cite
|
Sign up to set email alerts
|

Solution-based Ag-doped ZnSe thin films with tunable electrical and optical properties

Abstract: Thin film transistors fabricated using ZnSe thin films synthesized using chemical bath deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…ZnSe, as a typical II–IV semiconductor, has received great attention due to its applications in short-wavelength lasers, blue laser diodes, color displays, light-emitting diodes, biomedical sensors, high-density optical storages, and photodetectors. , ZnSe is the direct bandgap semiconductor, crystallized in face-centered cubic zincblende (ZB) and hexagonal wurtzite (WZ) phases. It has stronger visible-light absorption than TiO 2 . Furthermore, the conduction band minimum of ZnSe is more negative than the TiO 2 , which manifests its applications in the solar cells and organic degradation. , Although the conduction band (CB) edge of ZnSe is suitable for the photocatalytic reduction of CO 2 , it shows low photocatalytic activity because of the recombination of photogenerated electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnSe, as a typical II–IV semiconductor, has received great attention due to its applications in short-wavelength lasers, blue laser diodes, color displays, light-emitting diodes, biomedical sensors, high-density optical storages, and photodetectors. , ZnSe is the direct bandgap semiconductor, crystallized in face-centered cubic zincblende (ZB) and hexagonal wurtzite (WZ) phases. It has stronger visible-light absorption than TiO 2 . Furthermore, the conduction band minimum of ZnSe is more negative than the TiO 2 , which manifests its applications in the solar cells and organic degradation. , Although the conduction band (CB) edge of ZnSe is suitable for the photocatalytic reduction of CO 2 , it shows low photocatalytic activity because of the recombination of photogenerated electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%
“…ZnSe, as a typical II−IV semiconductor, has received great attention due to its applications in short-wavelength lasers, blue laser diodes, color displays, light-emitting diodes, biomedical sensors, high-density optical storages, and photodetectors. 8,9 ZnSe is the direct bandgap semiconductor, crystallized in face-centered cubic zincblende (ZB) and hexagonal wurtzite (WZ) phases. It has stronger visible-light absorption than TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc-based semiconductor nanostructures have attracted much more attention among various semiconductors due to application in the field of optoelectronics. , Zinc selenide (ZnSe; band gap, 2.67 eV) is considered as an excellent candidate for photodetectors, blue laser diodes, light-emitting diodes, sensors, and photocatalysts. , However, the low electrical conductivity and carrier mobility in ZnSe are the main disadvantages in the field of optoelectronic application. Recent studies have shown that forming composite with carbon nanotubes or graphene is a pathway to sort out this problem. ,, Charge carrier mobility (μ), like other transport parameters, is of great importance for semiconductor device applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the obtained films could be characterized by using several techniques such as spectroscopic ellipsometry 1,2 , Raman Spectroscopy [3][4][5] ,electrochemical impedance spectroscopy [6][7][8] ,profilometer 9,10 , R u t h e r fo r d backscattering spectrometry [11][12][13][14] , scanning tunneling microscopy [15][16][17] , and atomic force microscopy [18][19][20] . These films exhibit excellent chemical, optical, physical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%